Implementasi Over the Air Update menggunakan Protokol SSDP untuk Pencarian Perangkat - Ahmad Wildan; Mochammad Hannats Hanafi Ichsan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
With the Over the Air (OTA) update method, firmware updates on IoT device can be done without having to visit the IoT device. IoT device that installed at home or in the building and using local network the firmware can be easily updated and discovered with SSDP protocol (Simple Service Discovery Protocol). SSDP protocol usage in this research is for IP identification from each node that connect with the local network so that each node's web server can be accessed using IP address. The web server of each node is used to update the firmware of the accessed node. From the tests carried out 60 times with different distances in 1 meter, 3 meters, 5 meters, 10 meters, 15 meters, and 20 meters, it can be seen from the three nodes, the smallest average delay for device discovery using SSDP is at 1 meter that is 520.6 - 521 ms and the largest average delay is at 15 meters which is 682.23 - 785 ms. Then for firmware updates for the 3 tested nodes, the smallest average delay is at 1 meter, which is 8309 - 9801.5 ms and the largest average delay is at 15 meters, which is 15911 - 28687.8 ms.